Recent Advances in Noncoding RNAs - Tutar, Lütfi (IntechOpen, 2022)
The discovery of noncoding RNAs (ncRNAs) is changed our understanding of genome, transcriptome, and interactions with proteome in a cell. Since the discovery of the first microRNA (miRNA) called lin-4 on Caenorhabditis elegans in 1993, our understanding of gene expression has deepened. Further miRNA discoveries have led to the investigation of new ncRNA families and their function, biogenesis, and interactions with other types of molecules. Recent developments in bioinformatics, public databases, sequencing technologies, and biochemical techniques have increased our understanding of the biogenesis, function, and interactions of ncRNAs. This book provides an overview of current ncRNA research dealing with human diseases and cancer and plant miRNAs.